2021
DOI: 10.1111/ajt.16186
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood socioeconomic deprivation, racial segregation, and organ donation across 5 states

Abstract: One in 10 people die awaiting transplantation from donor shortage. Only half of Americans register as organ donors. In this cross‐sectional study, we evaluated population‐level associations of neighborhood socioeconomic deprivation and racial segregation on organ donor registration rates. We analyzed state identification card demographic and organ donor registration data from 5 states to estimate the association between a neighborhood socioeconomic deprivation index (range [0, 1]; higher values indicate more d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…This study adds to a growing body of literature suggesting that social and environmental context are relevant and important for transplant outcomes. [ 2,3,8,11,18,19 ] Taken together, these studies highlight that adverse social determinants of health are important predictors of morbidity and mortality for children undergoing LT. Disparities begin before wait‐list entry and extend through the long‐term posttransplant period.…”
Section: Discussionmentioning
confidence: 96%
“…This study adds to a growing body of literature suggesting that social and environmental context are relevant and important for transplant outcomes. [ 2,3,8,11,18,19 ] Taken together, these studies highlight that adverse social determinants of health are important predictors of morbidity and mortality for children undergoing LT. Disparities begin before wait‐list entry and extend through the long‐term posttransplant period.…”
Section: Discussionmentioning
confidence: 96%
“…However, ZIP codes are readily available within the SRTR database and define relatively small geographical areas. As more evidence accumulates that neighborhood context is important and relevant to transplant outcomes, 2,3,17 regulatory bodies should consider incorporating fixed geographical units (e.g., census blocks or census tracts) into the SRTR database. Second, the focus of this study was on the confluence of transplant center quality, neighborhood deprivation, and long‐term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The index, underlying measures, and the code used are publicly available 11 . Methods for the development and use of the deprivation index are described elsewhere 2,3,8,17 . To derive the patient‐mix deprivation index, we first matched the neighborhood deprivation index to patient home ZIP codes as reported to SRTR at the time of transplant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We need to communicate with people from all socioeconomic status and underrepresented minorities who may have received biased and unequal access to medical treatment resulting in lower life expectancy (Campbell et al 2020 ; da Rocha et al 2017 ; Rajah et al 2014 ; Steinecke and Terrell 2010 ). Studies have shown that most (Boulware et al 2004 ; Wadhwani et al 2021 ) of the human body or organ donors or people willing to donate their bodies or organs in the US are non-Hispanic White. This is due to the systemic racism embedded in our society and dedicated resources are needed to break this perpetual cycle.…”
Section: Tip 10: Growth and Developmentmentioning
confidence: 99%